Paternal and maternal stress in caring for children with learning disabilities in inclusive basic schools in Abuja, Nigeria - Olabisi, Akinola Patrick; Daud, Mohd Najmi; Ahmad, Sa’odah (RSIS International, 2024)
The present study evaluated paternal and maternal stress levels while taking care of their children with learning disabilities in Inclusive Basic Schools in Abuja, Nigeria. The study adopted a descriptive survey design. The study population was 2007 parents of children with learning disabilities from twenty (20) Inclusive Basic Schools across the six Area Councils of the Federal Capital Territory (FCT). Three hundred fourteen (314) samples were recruited using the Krejcie and Morgan formula. Parental Stress Scale (PSS) by Berry and Jones (1995) was utilized to measure stress levels among the samples. Descriptive statistics was employed in data analysis using the Statistical Package for Social Sciences (SPSS) version 23.0. Results revealed that the mother had a stress mean score of 48.39±5.68 and the father had a stress mean score of 48.83±5.33 with a t-value of -0.710 and a p-value of 0.478. Since the p-value is greater than 0.05, it means that there is no significant difference between the mean score of the stress of the mother and the father while taking care of their children with learning disabilities. The study recommends that fathers with high stress levels should be involved in the stress management group available in inclusive basic schools. In addition, school administrators should provide training programs for parents of children with learning disabilities in inclusive basic schools towards alleviating their stress due to caregiving.